(untitled) (Itinera, 2019)
The paper aims to analyse the possibilities of an emotional political theatre, which finds its roots in poetry of Artaud’s rather than Brecht’s. Two stagings of Christopher Marlowe’s The Massacre at Paris are analysed: the first directed by Patrice Chéreau at the Théâtre National Populaire in 1972 (Massacre à Paris) and the second by Ricci/Forte staged in 2016 (La strage di Parigi). Despite the aesthetic and time differences both staging aim to actualise Marlowe’s play through sensorial stimulation (smell and touch) and allusions to contemporary ideological murders.